Lipase and omega-transaminase catalysis in preparation of alcohol and amine enantiomers - Päiviö, Mari (Annales Universitatis Turkuensis D 1126, 2014)
Enantiopure intermediates are of high value in drug synthesis. Biocatalysis alone or combined with chemical synthesis provides powerful tools to access enantiopure compounds. In biocatalysis, chemo-, regio- and enantioselectivity of enzymes are combined with their inherent environmentally benign nature. Enzymes can be applied in versatile chemical reactions with non-natural substrates under synthesis conditions. Immobilization of an enzyme is a crucial part of an efficient biocatalytic synthesis method. Successful immobilization enhances the catalytic performance of an enzyme and enables its reuse in successive reactions. This thesis demonstrates the feasibility of biocatalysis in the preparation of enantiopure secondary alcohols and primary amines. Viability and synthetic usability of the studied biocatalytic methods have been addressed throughout this thesis. Candida antarctica lipase B (CAL-B) catalyzed enantioselective O-acylation of racemic secondary alcohols was successfully incorporated with in situ racemization in the dynamic kinetic resolution, affording the (R)-esters in high yields and enantiopurities. Side reactions causing decrease in yield and enantiopurity were suppressed. CAL-B was also utilized in the solvent-free kinetic resolution of racemic primary amines. This method produced the enantiomers as (R)-amides and (S)-amines under ambient conditions. An in-house sol-gel entrapment increased the reusability of CAL-B. Arthrobacter sp. omega-transaminase was entrapped in sol-gel matrices to obtain a reusable catalyst for the preparation enantiopure primary amines in an aqueous medium. The obtained heterogeneous omega-transaminase catalyst enabled the enantiomeric enrichment of the racemic amines to their (S)-enantiomers. The synthetic usability of the sol-gel catalyst was demonstrated in five successive preparative kinetic resolutions.

Lääkeainesynteesissä enantiopuhtaat intermediaatit ovat olennaisen tärkeitä. Biokatalyysi sellaisenaan tai yhdistettynä kemialliseen synteesiin mahdollistaa enantiopuhtaiden yhdisteiden valmistamisen. Biokatalyysissä yhdistyy entsyymien kemo-, regio- ja enantioselektiivisyys sekä entsyymien luontainen ympäristöystävällisyys. Entsyymejä voidaan hyödyntää lukuisten niiden tavanomaisista substraateista poikkeavien yhdisteiden reaktioissa vaativissa olosuhteissa. Entsyymien immobilisointi on olennainen osa tehokasta biokatalyyttistä synteesimenetelmää. Entsyymi-immobilisoinilla voidaan parantaa entsyymin ominaisuuksia ja mahdollistaa entsyymin uudelleenkäyttö useammissa peräkkäisissä reaktioissa. Väitöskirjassa tarkastellaan biokatalyysin käyttökelpoisuutta enantiopuhtaiden sekundaaristen alkoholien ja primaaristen amiinien valmistuksessa. Sekundaaristen alkoholien dynaamisessa kineettisessa resoluutiossa Candida antarctican lipaasin B (CAL-B) katalysoima enantioselektiivinen O-asylaatio yhdistettiin in situ rasemointiin. Menetelmä mahdollisti useiden (R)-esterien valmistamisen korkealla saannolla. Saantoon ja tuotteen enantiopuhtauteen vaikuttavien sivureaktioiden osuutta pienennettiin merkittävästi. CAL-B katalysoi myös primaaristen amiinien kineettistä resoluutiota liuotinvapaissa reaktio-olosuhteissa. Menetelmän avulla enantiomeerit valmistettiin (S)-amiineina ja (R)-amideina ympäristön olosuhteissa. Sooligeeli-immobilisointi lisäsi entsyymin kierrätettävyyttä. Arthrobacter-lajin omega-transaminaasi immobilisoitiin sooligeeliin. Tällöin saatiin heterogeeninen katalyytti, jota voitiin käyttää primaaristen amiinien valmistamiseksi (S)-enantiomeereina vesiliuoksissa. Immobilisointi mahdollisti entsyymin tehokkaan uudelleenkäytön viidessä peräkkäisessä preparatiivisessa reaktiossa.